A Comparative Study of Clinical Intervention and Interventional Photothermal Therapy for Pancreatic Cancer. Issue 33 (6th July 2017) - Hu, Yanyan; Chi, Chongwei; Wang, Shunhao; Wang, Lingxiong; Liang, Ping; Liu, Fangyi; Shang, Wenting; Wang, Weiwei; Zhang, Fengrong; Li, Shanshan; Shen, Heyun; Yu, Xiaoling; et al.
Abstract : Although nanoparticle‐based photothermal therapy (PTT) has been intensively investigated recently, its comparative efficiency with any clinical cancer treatments has been rarely explored. Herein for the first time we report a systematic comparative study of clinical iodine‐125 ( 125 I) interstitial brachytherapy (IBT‐125‐I) and interventional PTT (IPTT) in an orthotopic xenograft model of human pancreatic cancer. IPTT, based on the nanoparticles composing of anti‐urokinase plasminogen activator receptor (uPAR) antibody, polyethylene glycol (PEG), and indocyanine green (ICG) modified gold nanoshells (hereinafter uIGNs), is directly applied to local pancreatic tumor deep in the abdomen. In comparison to IBT‐125‐I, a 25% higher median survival rate of IPTT with complete ablation by one‐time intervention has been achieved. The IPTT could also inhibit pancreatic tumor metastasis which can be harnessed for effective cancer immunotherapy. All results show that this IPTT is a safe and radical treatment for eradicating tumor cells, and may benefit future clinical pancreatic cancer patients. Abstract : Gold nanoshells conjugated with anti‐urokinase plasminogen activator receptor (uPAR) antibody, poly(ethylene glycol) (PEG), and indocyanine green (ICG) are successfully synthesized. The synthesized nanomaterials are capable of actively targeting uPAR‐overexpressing pancreatic tumors. A novel interventional photothermal therapy method based on this nanomaterial is developed and it is demonstrated that this approach represents a safe method for eradicating pancreatic tumor cells.